Seasonal Epidemiological Surveillance on Bacterial and Fungal Pathogens in Broiler Farms in Egypt - Soliman, Essam S.; Sobeih, Mohamed A.A.; Ahmad, Z.H.; Hussein, M.M.; Abdel-Latiff, H.; Moneim, A.A. (International Journal of Poultry Science, 2009)
A total of 1664 environmental samples (litter, water, swabs and air) were collected from commercial broiler farms located in Ismailia and Zagazig Governorates, Egypt. The bacterial and Fungal isolates that were identified included: Citrobacter Sp, E. coli, Klebsiella oxytoca, Proteus vulgaris, Pseudomonas aureuginosa, Salmonella Sp, Shigella Sp, Staphylococcus aureus, Streptococcus fecalis and Streptococcus pneumonie, Yeast Sp, Pencillium Sp, Aspergillus niger, Aspegillus flavus, Aspergillus nidulans, Mucour and Candida albicans Prevalence and frequencies of the microorganisms were calculated to detect the most predominant microorganisms. Litter samples showed that Pseudomonas areuginosa (24%) and Yeast Sp (37.5%) predominated in closed houses; Klebsiella oxytoca (12%) and Penicillium Sp (28.57%) predominated in open houses in winter, Klebsiella oxytoca (33.33%) and Aspergillus nidulans (22.73%) predominated in closed houses; E. coli (50%) and Penicillium Sp (21.40%) in open houses in spring, Shigella Sp (34.5%); (47.62%) and Aspergillus niger (26.92%); (8.69%) predominated in closed and open houses respectively in summer, Klebsiella oxytoca (55.56%) and Aspergillus niger (12%) predominated in closed houses; Klebsiella oxytoca (41.67%) and Candida albicans (59.1%) predominated in open houses in autumn. Water samples showed that E. coli (39.47%) and Candida albicans (50%) predominated in closed houses; E. coli (60.97%) and Penicillium Sp (60%) predominated in open houses in winter, E. coli (67.57%) and Penicillium Sp (37.5%) predominated in closed houses; E. coli (89.29%) and Aspergillus nidulans (15.83%) predominated in open houses in spring, Shigella Sp (42.55%) and Penicillium Sp (37.5%) predominated in closed houses; Shigella Sp (36.67%) and Yeast Sp (66.6%) predominated in open houses in summer, Klebsiella oxytoca (36.59%) and Candida albicans (33.3%) predominated in closed houses; Klebsiella oxytoca (47.22%) and Candida albicans (47.62%) predominated in open houses in autumn. Swab samples showed that Pseudomonas areuginosa (62.5%) and Penicillium Sp (29.41%) predominated in closed houses; Pseudomonas aureuginosa (47.06%) and Candida albicans (17.64%) predominated in open houses in winter, Klebsiella oxytoca (36.49%) and Aspergillus flavus (43.48%) predominated in closed samples; E. coli (43.48%) and Aspergillus flavus (46.51%) predominated in open houses in spring, Klebsiella oxytoca (28.98%) and Penicillium Sp (34.48%) predominated in closed houses; E. coli (35.17%) and Aspergillus niger (35.14%) predominated in open houses in summer, Pseudomonas areuginosa (31.75%); (42.31%) and Canidada albicans (40.32%); (61.4%) predominated in closed and open houses respectively in autumn. Air samples showed that staphylococcus aureus (51.72%-45.45%, 52%-56.17%, 59.52-69.44 and 48.78-75%) was predominating in closed and open houses respectively in winter, spring, summer and autumn respectively, while the fungal growth showed that Aspergillus niger (66.6%) predominated in closed houses in winter, Aspergillus niger (100%) predominated in closed houses; Aspergillus favlus (100%) predominated in open houses in spring, Aspergillus niger (100%) predominated in closed houses in summer, Aspergillus niger (100%) predominated in closed and open houses in autumn.